2014
DOI: 10.1093/tropej/fmu025
|View full text |Cite
|
Sign up to set email alerts
|

Is Continuous Positive Airway Pressure a Feasible Treatment Modality for Neonates with Respiratory Distress Syndrome in a Rural District Hospital?

Abstract: nCPAP for neonatal respiratory distress at the district hospital is feasible, safe and offers the potential for significant cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…Several studies addressed secondary outcomes (reduction in need for mechanical ventilation via an endotracheal tube,37–39 and safety and efficacy of bubble CPAP compared with ventilator-driven CPAP35 40 41), while the largest number were case-series describing practical experience with CPAP, both bubble-based or via other systems 31 32 34 42–48. All studies described the use of CPAP in hospitals, with no studies describing home CPAP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies addressed secondary outcomes (reduction in need for mechanical ventilation via an endotracheal tube,37–39 and safety and efficacy of bubble CPAP compared with ventilator-driven CPAP35 40 41), while the largest number were case-series describing practical experience with CPAP, both bubble-based or via other systems 31 32 34 42–48. All studies described the use of CPAP in hospitals, with no studies describing home CPAP.…”
Section: Resultsmentioning
confidence: 99%
“…Among 571 neonates treated with CPAP of any kind with the potential for mechanical ventilation access (either in the same hospital or via transfer to nearby referral hospitals), the mortality rate was 83/571 (14.5%) 31 32 34 42–44 46–48. Of the 343 neonates for whom CPAP failure data are available, 110 (32.1%) failed CPAP therapy and required mechanical ventilation 31 32 34 42 43 47. Due to small numbers, it was difficult to determine the effect of birth weight on failure rate and mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Recently a report from a district hospital showed that managing patients outside a NICU is possible, improves outcomes and gives an opportunity to offer support while waiting for transport for transfer to a facility with NICU. [16] This suggests that CPAP can be safely used in resource-limited settings as the first line of therapy, with great benefits. Forty-eight percent of patients who were managed with NCPAP in this report also required exogenous surfactant.…”
Section: Discussionmentioning
confidence: 99%